(untitled) (Bangladesh Journal of Microbiology, 2012)
Aeromonas hyrophila strains AHV1, AHV2 and AH3 were isolated and identified from Muscle tissue, intestine, body fluid and gills of infected gold fish Carassius auratus. In order to study their virulence, LD50 tests against normal gold fish, proteolytic, haemolytic and challenge studies were performed. The virulence studies revealed that, both AHV1 and AHV2 strains are highly positive for proteolytic and haemolytic properties. The LD50 data showed that, the fish C. auratus are highly susceptible to A. hyrophila strains AHV1 and AHV2 at cent percent lethal rate. The survival of C. auratus significantly (P<0.05) decreased when challenged with virulent strains of A. hydrophila AHV1 and AHV2. The outer membrane protein (OMP-TS) gene was successfully amplified generating an the amplicon size of 1008 bp. The amplified product from the genomic DNA of AHV1 strain was cloned in to pTZ57R/T vector, transformed into DH5? cells and sequenced. The sequenced clone is resembling to various A. hydrophila isolates and submitted to NCBI GenBank database (accession no:HQ331525). DOI: http://dx.doi.org/10.3329/bjm.v28i2.11819 Bangladesh J Microbiol, Volume 28, Number 2, December 2011, pp 70-75